1997
DOI: 10.1007/s003830050125
|View full text |Cite
|
Sign up to set email alerts
|

Separation of ischiopagus tetrapus conjoined twins in the Sultanate of Oman

Abstract: Premature male ischiopagus tetrapus twins weighing 2.2 kg were born unexpectedly. They required initial ventilation for respiratory distress syndrome and an emergency laparotomy for intestinal obstruction at 10 days of age. At 8 months of age, formal separation was carried out. Primary skin closure was possible without the use of any tissue expander. Anaesthesia was supplemented with continuous intra- and post-operative epidural analgesia, with great benefit. Both twins are alive and well 18 months after surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Conjoined twinning is more common in females, with a 3:1 sex ratio [2,3]. Some authors have suggested a racial difference, with conjoined twins said to be more common among black Africans [7,10].…”
Section: Classificationmentioning
confidence: 99%
“…Conjoined twinning is more common in females, with a 3:1 sex ratio [2,3]. Some authors have suggested a racial difference, with conjoined twins said to be more common among black Africans [7,10].…”
Section: Classificationmentioning
confidence: 99%